Lexical and Phonological Processes in Dyslexic Readers: Evidence from a Visual Lexical Decision Task. (1st October 2013) - Araújo, Susana; Faísca, Luís; Bramão, Inês; Petersson, Karl Magnus; Reis, Alexandra
<x xml:space="preserve">Abstract</x> The aim of the present study was to investigate whether reading failure in the context of an orthography of intermediate consistency is linked to inefficient use of the lexical orthographic reading procedure. The performance of typically developing and dyslexic Portuguese‐speaking children was examined in a lexical decision task, where the stimulus lexicality, word frequency and length were manipulated. Both lexicality and length effects were larger in the dyslexic group than in controls, although the interaction between group and frequency disappeared when the data were transformed to control for general performance factors. Children with dyslexia were influenced in lexical decision making by the stimulus length of words and pseudowords, whereas age‐matched controls were influenced by the length of pseudowords only. These findings suggest that non‐impaired readers rely mainly on lexical orthographic information, but children with dyslexia preferentially use the phonological decoding procedure—albeit poorly—most likely because they struggle to process orthographic inputs as a whole such as controls do. Accordingly, dyslexic children showed significantly poorer performance than controls for all types of stimuli, including words that could be considered over‐learned, such as high‐frequency words. This suggests that their orthographic lexical entries are less established in the orthographic lexicon. Copyright © 2013 John Wiley & Sons, Ltd.